Sensorial characteristics of noodles incorporated with local Dabai fruit (Canarium odontophyllum) powder - Abdul Shukri, Farah Syahirah; Wei, Yii Hung; Abidin, Mohd Zahid; Hashim, Norhashila; Radzuan, Mohd Nazren; Pak Dek, Mohd Sabri (UTS Publisher, 2022)
Noodles are different from pasta and can be differentiated based on their ingredients and manufacturing processes. Noodles are made from common wheat flour and have high popularity among the Asian countries. The objective of this study is to evaluate the sensory properties of noodles incorporated with local Dabai fruit (Canarium odontophyllum) powder. In this study, noodles were prepared with three different level percentages (10%, 20%, and 30%) of Dabai powder as wheat flour substitution. The four-formulation including a control were evaluated for the sensory properties in terms of colour, aroma, taste, texture, overall acceptability and purchase intention. Among all the formulations, Dabai noodles of formulation 1 (10% Dabai) showed significant overall preference by the panelists. Panelists found that noodles incorporated with 10% Dabai powder are attractive for normal consumer while noodles incorporated with 30% Dabai powder are appealing for Dabai fruits lovers considering the aroma and taste as well.